Intertribal Marriage in Modernity: An Analysis from the Perspective of Islamic Family Law - Abdul Aziz (International Journal of Sharia Studies, 2025)
In Islam, there are four main aspects in choosing a life partner: wealth, beauty, lineage, and religion. However, amidst the current of modernity, social and cultural factors still play a significant role in determining this choice. This study aims to examine the factors underlying the tendency of people to engage in inter-tribal marriage in Sampaimah Village, Manyak Payed District, Aceh Tamiang Regency, and examine it from the perspective of Islamic family law. The method used is a qualitative descriptive approach with a field approach. Primary data were obtained through observation and interviews with local residents, while secondary data came from Islamic legal literature and fiqh books related to marriage. The results show that the preference for inter-tribal marriage is influenced by concerns about social conflict, racial discrimination, differences in customs, and social inequality that can trigger household disharmony. The community believes that ethnic similarity can minimize differences of opinion and maintain family harmony amidst modern social change. From the perspective of Islamic family law, the practice of inter-tribal marriage is valid according to sharia because it fulfills the pillars and requirements of marriage. However, the tendency to avoid inter-tribal marriage does not have a strong legal basis in Islam. The concept of kafaah emphasizes equality in religion and morals, not ethnicity. Therefore, a deeper understanding is needed so that Islamic values ​​become the primary basis for choosing a life partner.